Migration and spatial development. - Postlep, Rolf-Dieter; Ritzinger, Anne; Spellerberg, Annette (My University, 2021)
The high influx of refugees confronts Germany with a variety of tasks and problems. In addition to short-term challenges such as geographically allocating and accommodating refugees, longer-term tasks involving housing, regional and integration policy also need to be addressed. Notwithstanding heavy financial burdens, claims that capacity limits will be exceeded, and growing problems with acceptance, refugees are people with a right to protection and to an individual review of their wish to stay. Many of the refugees already in Germany will not be able to return to their home countries in the foreseeable future due to the precarious situation there, so integration strategies with at least a medium-term focus need to be developed. The extent to which it is currently appropriate for migration policy to also support long-term settlement strategies is a matter for separate discussion.
Keywords: Migration; Einwanderung; Regionalentwicklung; Raumentwicklung; Soziale Integration; Wirkungsanalyse